Enhanced sustained release of furosemide in long circulating chitosan-conjugated PLGA nanoparticles - Kashyap, S.; Singh, A.; Mishra, A.; Singh, V. (Wolters Kluwer Medknow Publications, 2019)
Furosemide (FSM) is commonly used in the treatment of edema associated with congestive cardiac failure, cirrhosis of the liver, renal disease, including the nephrotic syndrome and hypertension. However, in ascites, it is clinically limited due to its frequent dosing and short biological half-life and its prolonged-release preparations are not available. Therefore, the main objective behind the present research work is to develop chitosan coated and conjugated poly (lactic-co-glycolic acid) (PLGA) nanocarriers, to sustain the delivery of FSM with improved systemic circulation. Emulsion-solvent evaporation technique was used for the preparation of nanoparticles. In-vivo pharmacokinetic study showed 2.6, 3.10, and 4.30 folds enhancement in relative availability of FSM for FSM-PLGA, FSM-chitosan-coated-PLGA and FSM-chitosan-conjugated-PLGA nanoparticles, respectively than FSM. The present research work concluded that FSM loaded chitosan conjugated PLGA nanoparticles could enhance the systemic circulation of FSM with improved pharmacokinetics parameters. © 2019 Medknow Publications.All rights reserved.
Keywords: Chitosan; FSM; Nanocarriers; PLGA; Polymeric nanoparticles; Sustained effect